Синонімія каузативних сполучників та прийменників в українських інформаційних медіатекстах воєнного періоду - Межов, Олександр; Костусяк, Наталія; Навальна, Марина (Slavia Orientalis, 2025)
The article presents a comprehensive analysis of the synonymy of conjunctions and prepositions as actualizers of causative semantic and syntactic relations and the pragmalinguistic potential of the corresponding syntactic constructions in information media genres. The complex subordinate clauses of the cause are singled out from the media texts and the semantic shades of causative synonymous conjunctions are revealed. The simple sentences with prepositional causative syntaxes are distinguished, their semantic and morphological variants are outlined. The correlative pairs of conjunctions and prepositions as the main grammatical markers of the category of cause are identified. The derivational relations of complex subordinate constructions and semantically complicated simple sentences in the field of causation are characterized. As the analyzed factual material shows, journalists of information media genres actively use the expressive possibilities of syntactic synonymy of causative conjunctions and prepositional structures in order to diversify their expressions, avoid the same type of syntactic structures and monotony of speech, and make it expressive. In constructing utterances, the speaker (author) chooses the most appropriate syntactic units (among synonymous or identical ones) for effective communication with the recipient in accordance with the illocutionary intention and the expected perlocutionary effect.